Information- and Communication Theory in Molecular Biology (Lecture Notes in Bioengineering,, 2018)
This edited monograph presents the collected interdisciplinary research results of the priority program "Information- and Communication Theory in Molecular Biology (InKoMBio, SPP 1395)", funded by the German Research Foundation DFG, 2010 until 2016. The topical spectrum is very broad and comprises, but is not limited to, aspects such as microRNA as part of cell communication, information flow in mammalian signal transduction pathway, cell-cell communication, semiotic structures in biological systems, as well as application of methods from information theory in protein interaction analysis. The target audience primarily comprises research experts in the field of biological signal processing, but the book is also beneficial for graduate students alike.